Electromagnetic wave effects on Mn-doped superparamagnetic iron oxide nanofluids: applications in enhanced oil recovery - Chan, Kar Tim; Beh, Hoe Guan; Hamid, Mohamad Amin; Hassan, Soleimani (Royal Society of Chemistry, 2024)
The utilization of superparamagnetic iron oxide nanofluids in enhanced oil recovery (EOR) has gained attention due to their ability to alter the interfacial tension (IFT) of reservoir rocks. However, the influence of electromagnetic (EM) waves on these nanofluids, particularly when doped with manganese (Mn), remains underexplored. The interaction mechanisms between EM waves and Mn-doped Fe3O4 nanofluids are not well understood, limiting their application in EOR. This study aimed to investigate the effects of EM waves on Mn-doped superparamagnetic iron oxide nanofluids and to assess the potential for enhancing oil recovery by measuring their IFT. Mn-doped Fe3O4 nanoparticles were synthesized using a co-precipitation method and stabilized with ascorbic acid. Density functional theory (DFT) was employed to study the Mn-dopant site selectivity within the Fe3O4 lattice. Helmholtz coils generated uniform EM fields and interfacial tension (IFT) measurements were conducted under applied EM waves generated under both direct current (DC) and alternating current (AC) conditions. DFT calculations indicated a preference for Mn dopants in specific lattice sites, while the experimental results showed that both DC- and AC-generated sinusoidal EM waves could reduce the IFT of the Mn-doped nanofluids, suggesting their improved EOR potential. These findings provide new insights into the application of EM waves in nanofluid-based EOR